2010
DOI: 10.1093/ajae/aap018
|View full text |Cite
|
Sign up to set email alerts
|

Technology Adoption and Technical Efficiency: Organic and Conventional Dairy Farms in the United States

Abstract: We compare productivity and technical efficiency of organic and conventional dairy farms in the United States. We address self-selection into organic farming by using propensity score matching and explicitly test the hypothesis that organic and conventional farms employ a single, homogeneous technology. Utilizing the 2005 Agricultural Resource Management Survey on Dairy Costs and Returns Report data, we reject the homogeneous technology hypothesis and find that the organic dairy technology is approximately 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
166
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(185 citation statements)
references
References 27 publications
14
166
5
Order By: Relevance
“…U.S. organic milk production costs shown to be $5 -$8/cwt higher than for conventional milk (McBride and Greene, 2009). No significant differences in technical efficiency found between U.S. organic and non-organic dairy farms (Mayen et al, 2010).…”
Section: Usda Certified Organic Milk Productionmentioning
confidence: 84%
“…U.S. organic milk production costs shown to be $5 -$8/cwt higher than for conventional milk (McBride and Greene, 2009). No significant differences in technical efficiency found between U.S. organic and non-organic dairy farms (Mayen et al, 2010).…”
Section: Usda Certified Organic Milk Productionmentioning
confidence: 84%
“…However, the two-step Heckman procedure is less suitable for non-linear functions such as the stochastic frontier. We therefore use matching techniques similar to Mayen, Balagtas, and Alexander (2010) in their stochastic frontier analysis.…”
Section: Potential Selection Biasmentioning
confidence: 99%
“…Madau (2007) and Tiede mann and LataczLohmann (2012) concluded that, organic agriculture is more technical inefficient than conventional agriculture. Mayen et al (2010) however intimated that, measured against the appropriate technology, organic and conventional agriculture (dairy) did not show any significant difference in technical inefficiency.…”
Section: Introductionmentioning
confidence: 94%